Commonly used medications for respiratory and cardiovascular support in neonates: Evidence, knowledge gaps, and future perspectives - Eleni Agakidou; Angeliki Kontou; Ilias Chatziioannidis; William Chotas; Kosmas Sarafidis (Elsevier, 2024)
Critically ill neonates admitted to neonatal intensive care units require specialized pharmacological treatment due to various medical conditions. However, despite the decades of clinical use of some pharmacological agents, there are still significant knowledge gaps surrounding their everyday use. The wide variability of drugs used in neonates, and how they are used in different settings worldwide, precisely reflects this fact. A major factor contributing to this variability is the lack of adequate studies regarding the effectiveness and safety of medications administered to neonates, especially in those born preterm. This is mainly due to inherent difficulties in performing pharmacokinetic, pharmacodynamic, and clinical studies in this age group. In this review, we discuss the existing data on medications most commonly used in the respiratory and cardiovascular care of the sick neonate. Knowledge gaps and future perspectives are highlighted, as well.